2019
DOI: 10.5539/jas.v11n5p70
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pochonia chlamydosporia (Goddard) Isolates for Suppression of Meloidogyne incognita, Root-Knot Nematode of Tomato

Abstract: Restricted applications of chemical nematicides has directed to the development of ecofriendly alternatives. Culture filtrates in different concentrations (20, 40, 60, 80 and 100%) of the six isolates of Pochonia chlamydosporia were evaluated for their nematicidal activity. Significant variations were observed in the inhibitory activity of culture filtrates against egg hatching and second stage juveniles of M. incognita at different concentrations. The culture extract of PC-6 showed maximum inhibition of egg h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Regaieg, et al 49 reported that mortality of juveniles was relative to the Verticillium leptobactrum filtrate concentrations and the duration of exposure. Similarly Uddin, et al 18 reported that the culture filtrate of fungus P. chlamydosporia was effected to control M. incognita. The practice of biocontrol agents may decrease the use of harmful chemicals.…”
Section: Discussionmentioning
confidence: 93%
“…Regaieg, et al 49 reported that mortality of juveniles was relative to the Verticillium leptobactrum filtrate concentrations and the duration of exposure. Similarly Uddin, et al 18 reported that the culture filtrate of fungus P. chlamydosporia was effected to control M. incognita. The practice of biocontrol agents may decrease the use of harmful chemicals.…”
Section: Discussionmentioning
confidence: 93%
“…También se obtuvo, con esta misma cepa, de 2 a 3x10 4 UFC g -1 de suelo en presencia de estrés salino moderado (Hidalgo-Díaz & Ceiro, 2017). Cantidades iguales o superiores a 10 3 UFC g -1 de P. chlamydosporia en los suelos de forma natural, favorecen la formación de los denominados suelos supresores de nematodos, los cuales no requieren de medidas adicionales de manejo para esta plaga (Uddin et al, 2019).…”
Section: Discussionunclassified
“…Many filamentous fungi can be utilized to suppress pathogenic growth (Baron et al, 2019) like the beneficial rhizofungus Coniothyrium minitans that possesses activity against the phytopathogen Sclerotinia sclerotiorum (Zeng et al, 2012). A suppressive activity has also been reported for the nematophage Pochonia chlamydosporia (formerly named Verticillium chlamydosporia) with strong antagonism against plant-pathogenic nematodes (Lin et al, 2018;Uddin et al, 2019). Also bacteria can be utilized as natural antagonists.…”
Section: Natural Rhizobacteria As Antagonists Of Microbial Pathogensmentioning
confidence: 99%
“…Verticillia that infect nematode cysts are grouped to Pochonia (Sung et al, 2001). The mutualistic nematophage Pochonia chlamydosporia (formerly named Verticillium chlamydosporia) is closely related to the opportunistic V. longisporum or V. dahliae and has been widely characterized as a nematode antagonist utilized as a biocontrol agent in agriculture (Lin et al, 2018;Uddin et al, 2019). Particularly interesting in this regard is the described biocontrol effect even within the Verticillium genus.…”
Section: The Positive and Negative Connotation Of Beneficials And Pat...mentioning
confidence: 99%